A high-resolution X-ray photoelectron spectroscopy study on the adsorption and reaction of ethylene on Rh(1 1 1) - Freiberger, Eva Marie; Düll, Fabian; Wichmann, Christoph; Bauer, Udo; Steinrück, Hans-Peter; Papp, Christian (Chemical Physics Letters, 2022)
The adsorption and thermal evolution of ethylene on Rh(1 1 1) were investigated by state-of-the-art surface science techniques. Synchrotron radiation-based high-resolution X-ray photoelectron spectroscopy (XPS) and temperature-programmed XPS allowed for the examination of the adsorption process and the reaction pathway of ethylene on Rh(1 1 1). At 140 K, ethylene adsorbs molecularly in a symmetrical geometry. The reaction intermediates formed upon heating were identified by the vibrational fine structure of XPS. At approximately 200 K, ethylidyne emerges, as expected from literature. Above 350 K, we observe the evolution of methylidyne. Simultaneously, decomposition to carbides sets in, which is completed at ∼ 460 K.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Coking; Ethylene; Ethylidyne; High-resolution X-ray photoelectron spectroscopy; Methylidyne; Rhodium; Unsaturated hydrocarbons; Vibrational fine structure